Signaling and functional competency of neutrophils derived from bone-marrow cells expressing the ER-HOXB8 oncoprotein. Issue 5 (19th June 2019) - Saul, Stephanie; Castelbou, Cyril; Fickentscher, Céline; Demaurex, Nicolas
Abstract: Neutrophils play a central role in immunity and inflammation via their intrinsic ability to migrate into inflamed tissue, to phagocytose pathogens, and to kill bacterial and fungi by releasing large quantities of superoxide anions and lytic enzymes. The molecular pathways controlling neutrophil microbicidal functions are still unclear, because neutrophils have a short half-life and are resistant to genetic manipulation. Neutrophil-like cells (NLC) can be generated from myeloid progenitors conditionally immortalized with the ER-HoxB8 oncoprotein, but whether these cells can replace neutrophils in high-throughput functional assays is unclear. Here, we assess the ability of NLC derived from ER-HoxB8 progenitors to produce ROS and to perform chemotaxis and phagocytosis. We compare the Ca 2+ responses and effector functions of NLC to primary murine neutrophils and document the molecular basis of their functional differences by mRNA profiling. Pro-inflammatory cytokines enhanced the expression by NLC of neutrophil surface markers and transcription factors. Ca 2+ elevations evoked in NLC by agonists, adhesion receptors, and store depletion resembled the physiological responses recorded in primary neutrophils, but NLC expressed reduced amounts of Ca 2+ signaling proteins and of chemotactic receptors. Unlike their myeloid progenitors, NLC produced H2 O2 when adhered to fibronectin, migrated toward chemotactic peptides, phagocytosed opsonized particles, and generated intracellular ROS. NLC phagocytosed as efficiently as primary neutrophils but produced 50 times less ROS and migrated less efficiently toward chemoattractant. Our data indicate that NLC can replace neutrophils to study Ca 2+ signaling and phagocytosis, but that their incomplete granulocytic differentiation limits their use for chemotaxis and ROS production assays. Graphical Abstract: Cytokine supplementation during differentiation of the ER-HoxB8 myeloid cell line resulted in an improved neutrophil-like phenotype, enabling high-throughput assays of Ca 2+ signals, phagocytosis, ROS production, and chemotaxis, but granule contents remained too low for degranulation assays.